UTILIZATION OF GOOD AGRICULTURAL PRACTICES TECHNOLOGIES AMONG TOMATO FARMERS IN OYO STATE, NIGERIA - John OYETORO; Afusat ALABI; Lateef JIMOH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study assessed the utilization of Good Agricultural Practices (GAPs among tomato farmers in Oyo State, Nigeria. Using three stage sampling technique, (240) registered tomato farmers were selected sample size for the study. Interview schedule was utilized to elicit relevant information and data were analysed using descriptive and inferential statistics. Results show that most (65.0%) of the respondents were males, married (50.0%) with mean age, household size and years of formal education of 35±10.5 years, 2 ± 0.6 persons and 13.0±3.9 years, respectively. Most (56.3%) of the respondents were primarily engaged in farming with mean annual income of ₦703,075.00 ±210,922.5 while few (42.5%) belong to social organisation. The most frequently aware of all the practices by the respondents were to look for pest and disease resistance varieties (93.8%) while inadequate knowledge of GAPs (1.46) and high cost of technology (1.29) were the main constraints to utilization of GAPs among tomato farmers in the study area. Positive relationship was found between age (r = 0.531, p≤0.05), years of formal education (r = 0.460, p≤0.05) and utilization of GAPs. The study concluded that GAPs were moderately utilized among the respondents and recommended that government should provide special incentives for the tomato farmers in order to encourage them as well as others who are yet to engaged in GAPs.